Analysis of Financial Ratios and Data Visualization of Share Prices in Coal Mining Company - Melissa Indah Fianty; Kevin Sullivan Gunawan (Universitas Islam Raden Rahmat, Malang, 2023)
Many novice investors do not analyze financial ratios and thus suffer many losses. Analyzing the fundamentals of financial ratios that can maximize investment returns, and see information on the current and future profits and health of the company. In addition to profits, there are also risks from stock investment. To reduce risk, analysis is needed to predict stock prices. The data used is the company's annual report with the correlation coefficient method with Tableau tools so that it can find the correlation between financial ratios and the company's stock price and visualize the data. The results showed that there is a strong positive relationship between the price of the company's shares and financial ratios so that this analysis can be used to predict stock prices and investors in making stock investment decisions.